Cistercian art and architecture in the British isles - Norton, Christopher; Park, David (Cambridge Univ. Press, 1986)
From their introduction in the early twelfth century the Cistercians were one of the leading monastic orders in Britain. Many of the finest monastic remains - Fountains, Rievaulx and Tintern - are Cistercian. This book is the first ever comprehensive survey of Cistercian art and architecture in the British Isles. The various contributions, all by leading specialists, cover the historical and literary background; the development of Cistercian architecture (especially in the twelfth and thirteenth centuries, when the Cistercians were in the forefront of architectural achievement, playing an important role in the introduction and dissemination of the Gothic Style); and art forms such as wall painting, stained glass, tile pavements, and manuscript illumination, as well as liturgy and music. These studies reveal what was distinctively Cistercian in the art and architecture of the Order, and permit a new understanding of the remarkable contribution of the Cistercians to the culture of medieval Britain.